The empirical study of sustainability reporting and financial performance of Malaysian public listed companies - Kasbun, Nur Fatin (2015)
This study examines the impact of sustainability reporting on financial performance among Malaysian public listed companies. A lot of companies across the globe have increasingly involved with sustainability reporting in recent years. Widely, it is not necessary because of the mandatory rules or for reputational issues anymore but it is one of the ways to create efficiency in a business and to improve its performance. The current problem of sustainability reporting is that companies are not convinced to report. When it comes to reporting, a company would contemplate of the additional cost and other uncertain issues that might incur. This results to the ignorance of sustainability. Due to the uncertain issues such as high reporting cost and the difficulty of measurements, the reporting has been neglected and certain people are unaware about the importance of sustainability. Another problem of sustainability reporting is that the reporting percentage is very low among developing countries in Asia including Malaysia. There is only a small percentage of reporting even though Malaysia is assumed to be on the highest rank in reporting sustainability among South East Asia countries. The sample of this study involved 200 companies selected from the Malaysian Public Listed Companies as its population involved 200 companies selected from the Malaysian Public Listed Companies as its population. Data collection acquired using the data stream, sustainability reports, annual reports and other means disclosing any companies' social, environmental and economic sustainability activities and from year of 2006 and 2013. The operationalization on sustainability data is according to Global Reporting Initiative (GRI) indicators. Content analysis is used to analyze the number of sentences reported by a company. A multiple regression analysis was employed to analyze the relationship of sustainability reporting and financial performance. The findings from regression analyses demonstrated that sustainability reporting in the fields of economic, environmental and social have a significant relation with companies' financial performance. Convincingly due to sustainability reporting reported by Malaysian Public Listed companies, the results indicate that when a company reports sustainability, it will attract more investors, as it is not only about making profits but to contribute to society as well. The findings suggest that, hence from attracting investors, it should be able to have a better performance financially and able to corresponding to stakeholders, shareholders, and community or citizen needs and remain sustainable in corporate world. Besides that, the findings also showed that sustainability reporting among Malaysian Public Listed Companies has tremendously improved from the year 2006 until 2013. Although the findings are varied, it answered the questions and objectives of this study which emphasized that sustainability reporting plays an important role in affecting financial performance of a company.